Natural nanotube-based biomimetic porous microspheres for significantly enhanced biomolecule immobilization - Chao, C.; Zhang, B.; Zhai, R.; Xiang, X.; Liu, Jian; Chen, R. (American Chemical Society, 2014)
Inorganic nanostructures and their assemblies play important roles in immobilizing biomolecules. Herein, we developed a facile and green methodology to assemble natural halloysite nanotubes (1D building blocks) into nest-like porous microspheres (3D architecture). We further modified the microspheres with dopamine to form a biomimetic entity. The interconnected and hierarchical pores within the microspheres provide larger pore volume to entrap biomolecules, and the abundant functional groups on the pore surface bond covalently with enzyme to enhance the immobilization ability. The porous microspheres showed excellent loading capacity for laccase immobilization as high as 311.2 mg/g, around 30 times higher than the individual halloysite nanotubes (11.3 mg/g). The specific activity above 80% was retained for the immobilized laccase compared to the free laccase. In addition, the immobilized enzyme exhibited remarkable thermal and recycle use stability. The biomimetic microspheres are expected to be biologically safe and chemically stable microcapsules for immobilizing a variety of biomolecules because of their natural and biofriendly characteristics. © 2013 American Chemical Society.